Sustainability practices in hospitality: Case study of a luxury hotel in Arrábida Natural Park - Pereira, V.; Silva, G. M.; Dias, Á. (Sustainability, 2021)
The agenda of researchers and practitioners in the tourism industry has focused on the demand for sustainable practices. Luxury hotels have also followed this trend, although studies are still limited. The aim of this study is to understand what environmental and social sustainability practices luxury hotels are adopting and how their management perceive the benefits and results from their adoption. This empirical research is based on a case study that triangulates data from semi-structured interviews, document analysis, and direct observations. The results show that luxury hotels have implemented environmental practices that address energy efficiency measures that reduce water consumption, waste, carbon emissions and that control, protect, and maintain fauna and flora to promote of unique natural landscapes. They have focused on social practices that address the relations with charitable institutions, provide consumers high-quality services, and create a safe and healthy work environment. Luxury hotels have successfully implemented these practices to reduce operational costs. The study’s findings provide practical guidance for hotel managers who seek to implement sustainability practices.